2021
DOI: 10.3390/toxins13120887
|View full text |Cite
|
Sign up to set email alerts
|

Pain Reduction in Adults with Limb Spasticity Following Treatment with IncobotulinumtoxinA: A Pooled Analysis

Abstract: Some studies have shown that incobotulinumtoxinA reduces spasticity-associated pain, but further evidence is needed. This exploratory analysis pooled pain-relief data from six Phase 2 or 3 studies of incobotulinumtoxinA (four placebo-controlled studies) for treating upper limb spasticity in adults. Spasticity-associated pain was assessed at baseline and 4 weeks post incobotulinumtoxinA injection using the disability assessment scale (DAS) for pain. Only data for patients with pain at baseline were analysed. Ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…In a recent pooled analysis, repeated incobotulinumtoxinA injections were demonstrated to be effective in reducing UL pain associated with spasticity regardless of baseline pain severity and showed a cumulative effect over time with a greater effect on pain observed after multiple injection cycles ( 2 ). When BoNT-A is introduced early after the onset of spasticity, pain reduction is rapid, being observed after a single BoNT-A injection ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent pooled analysis, repeated incobotulinumtoxinA injections were demonstrated to be effective in reducing UL pain associated with spasticity regardless of baseline pain severity and showed a cumulative effect over time with a greater effect on pain observed after multiple injection cycles ( 2 ). When BoNT-A is introduced early after the onset of spasticity, pain reduction is rapid, being observed after a single BoNT-A injection ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…Botulinum neurotoxin type A (BoNT-A) is an established first-line treatment in focal, multifocal, and segmental spasticity to provide pain relief, to reduce involuntary movements, and to help restore both passive and active functions (1)(2)(3). Most pivotal trials with BoNT-A in the upper limb (UL) spasticity did not include the injection of shoulder muscles (4)(5)(6)(7)(8)(9), although a few recent trials reported the benefits of including shoulder muscles as possible injection targets (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Spastic movement disorder, as defined by Pandyan et al (1) and herein termed "spasticity", consists of all positive symptoms of upper motor neuron syndrome (UMNS) -normally characterized by increased levels of involuntary motor activity, and including spasticity (a velocity-dependent increase in muscle tone) and spastic dystonia (1)(2)(3). Upper limb (UL) spasticity has been reported to affect as many as 43% of patients up to 12 months post-stroke (4,5) and may be associated with pain following stretching of the muscles and soft tissue involved, deformity, impairment and/or loss of limb function (6,7). This can negatively impact quality of life (QoL) due to the need to depend on others (8) as well as resulting in social isolation and depression (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Botulinum neurotoxin A (BoNT-A) is first-line treatment for focal, multifocal and segmental spasticity and provides pain relief for those with spasticity-associated pain, reduces involuntary movements in UMNS and helps to restore both passive and active function ( 7 , 12 , 13 ). Furthermore, treatment with BoNT-A has been shown to improve patient QoL and has a superior cost-utility ratio compared with conventional oral antispastic therapy in UL spasticity ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation